2005
DOI: 10.1139/f04-246
|View full text |Cite
|
Sign up to set email alerts
|

Escapement, harvest, and unknown loss of radio-tagged adult salmonids in the Columbia River – Snake River hydrosystem

Abstract: Accurate estimates of escapement by adult anadromous salmonids are difficult, especially in large, multistock river systems. We used radiotelemetry and a fishery reward program to calculate escapement, harvest, and unaccounted for loss rates for 10 498 adult chinook salmon (Oncorhynchus tshawytscha) and 5324 steelhead (Oncorhynchus mykiss) during six return years in the Columbia River basin. Mean annual escapements to spawning sites, hatcheries, or the upper bounds of the monitored hydrosystem were 73.4% (spri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
69
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(72 citation statements)
references
References 43 publications
3
69
0
Order By: Relevance
“…Descriptions of fish capture, anesthetization, intragastric tagging methods, handling and release protocols, and transmitter specifications are provided in Keefer et al (2004aKeefer et al ( , 2005. Briefly, the trap facility was located adjacent to the north-shore fish ladder.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Descriptions of fish capture, anesthetization, intragastric tagging methods, handling and release protocols, and transmitter specifications are provided in Keefer et al (2004aKeefer et al ( , 2005. Briefly, the trap facility was located adjacent to the north-shore fish ladder.…”
Section: Methodsmentioning
confidence: 99%
“…This basic estimate required no assumptions about whether captured fish would have passed the dam in the same statistical week, although median tailrace and dam passage times for radio-tagged Chinook salmon were 0.9-1.4 d (Keefer et al 2004a). Seasonal (winter = weeks 1-11, spring = weeks 12-22) and annual (1 January to 31 May) predation estimates treated captured fish as part of the salmonid count total [i.e., predation rate = Catch Total / (Count Total + Catch Total )] based on the assumption that almost all salmonids captured in the tailrace would have passed upstream eventually in the absence of predators (Keefer et al 2005). Uncertainty associated with overwintering steelhead abundance and behavior resulted in relatively lower Downloaded by [Queensland University of Technology] at 18:36 20 November 2014 confidence in winter versus spring predation rate estimates.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We observed a higher "dropout" rate in the BON-to-MCN reach for returning adults that as smolts were transported. An overall lower escapement was estimated in the BON-to-MCN was also observed in the radio-tag studies by Keefer et al (2005) using returning adults of known origin based on PIT-tags (as well as fish of unknown origin) that were then fitted with radio tags at BON and monitored on their upstream migration. In that study both mainstem and tributary harvest was taken into account, and they found "reach (dam-to-dam) escapement estimates were lowest in the lower Columbia River and were highest in the lower Snake River."…”
Section: Fish Passage Centermentioning
confidence: 60%
“…Detections of radio-tagged fish at tributary sites were used to help determine which salmon entered and remained in tributaries during spawning seasons. Records from dam, reservoir, main stem (i.e., Hanford Reach), and mobile-tracking surveys, plus transmitter returns from fisheries (reward-based), hatcheries, traps and spawning ground surveys were also used to establish fish distribution and fate (see Keefer et al, 2005 andJepson et al, 2010). Detection efficiencies were near 100% at dams and were >90% at almost all tributary antennas.…”
Section: Salmon Monitoring and Tag Recoverymentioning
confidence: 99%